Development of UTAUT-based augmented reality acceptance scale: a validity and reliability study - Üstün, Ahmet Berk; Karaoğlan Yılmaz, Fatma Gizem; Yılmaz, Ramazan; Ceylan, Mehmet; Uzun, Orhan; Yılmaz, Ramazan; Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem; Üstün, Ahmet Berk (Springer, 2024)
The primary aim of the study is to develop an augmented reality (AR) acceptance scale within the framework of the unified theory of acceptance and use of technology (UTAUT) model to measure individuals' acceptance and use of AR technology. The study was performed with a total of 546 university students with three participant groups in the 2022-2023 academic year. Reliability and validity studies of the scale were also carried out. The face validity and content validity of the scale were investigated by receiving constructive feedback from various field experts. To scrutinize the construct validity, exploratory factor analysis (EFA) was applied to the first participant group (n = 315) while confirmatory factor analysis (CFA) was conducted with the second participant group (n = 182). The EFA results confirmed the four-factor structure with 21 items accounting for 71.86% of the total variance, while the CFA results showed that the four-factor model had a sufficient fit. The reliability of the UTUAT-based AR acceptance measurement tool was investigated using Cronbach's alpha and test-retest methods. The Cronbach's alpha coefficient of the scale was 0.95 whereas the test-retest reliability of the tool was 0.97. To investigate the discriminative power of the items, corrected item-total correlations and 27% upper and lower comparison of the participants were made. In conclusion, the UTUAT-based AR acceptance measurement tool is valid and reliable in measuring users' AR acceptance and use levels.
Keywords: Augmented Reality; Technology Acceptance; Augmented Reality Acceptance; Augmented Reality Acceptance Instrument; Utaut